Kształtowanie kompetencji społecznych na kierunku lekarskim w ramach przedmiotów humanistycznych - Wiśniewska, Danuta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In connection with the implementation of the NQF as part of the education process concentration on learning outcomes in terms of knowledge, skills and personal and social competence became. At the moment, there is a gradual increase of interest among employers’ social competence of university graduates, which determine, in their opinion the effective implementation of teamwork, interpersonal communication and group etc. Accordingly, it became an important answer to the question about the process of shaping those powers on the selected field of study, which particularly characterized by the need for development of social skills in the learning process. The first part contains the characteristics of legal regulations concerning the medical in Poland. The second part focuses on developing social skills in the context of the humanities subjects in medicine.
Keywords: efekty kształcenia; kierunek lekarski; kompetencje społeczne; przedmioty humanistyczne